The Gains from Import Variety in Two Globalisations: Evidence from Germany - Wolf-Fabian Hungerland (European Historical Economics Society (EHES), 2017)
What are the gains from trade today compared to those in the globalisation hundred years ago? To answer this question I rely on Krugman's (1980) idea that consumers value growing import variety, and very granular German product-level data from the first globalisation (ahead of World War I), and today. First, I derive structural estimates of the elasticity of substitution at the product-level for both globalisation episodes. I find substantial heterogeneity in terms of how elastic demand over goods and their varieties is, especially when compared over the long run. The median elasticity is 3.8 in the first globalisation, but only 2.5 in the second. This suggests that demand was more elastic in the first globalisation and that the structure of demand is not easily approximated by using a single elasticity of substitution, which is often done in the literature. Second, I use these estimated elasticities and calculate the consumer gains from growing import variety ahead of World War I and for today. The welfare calculations suggest that the gains from trade in the first globalisation are twice as much as today. Welfare turns out much lower—falling down to a fifth of the benchmark— when using non-contemporary, that is, inadequate elasticities. Simply taking one single elasticity or a set of ahistorical elasticities can be easily misleading because gains from international trade as well as the effects of changes in trade costs may be wrongly captured.
Keywords: F12; F14; F61; N33; N74; 330; Product variety; elasticity of substitution; gains from trade; first globalisation